Book Review - Susan Feez (University of Kansas, 2023)
A century on, as young children in Montessori classrooms around the world continue to engage with Sandpaper Letters, Metal Insets, Moveable Alphabets, and Reading Command cards, an accumulation of studies into how children learn to read from across a range of disciplines has generated an influential body of research evidence that has been dubbed the science of reading. The science of reading is currently being used to shape education policy and mandated curriculum documents, especially in the English-speaking world. For this reason, the comparative analysis of the Montessori approach and the science of reading presented in Powerful Literacy in the Montessori Classroom: Aligning Reading Research and Practice will be welcomed by many Montessori educators.